2003
DOI: 10.1097/00001888-200310001-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Postgraduate Training and Timing on USMLE Step 3 Performance

Abstract: Study data reaffirm the validity of the USMLE Step 3 examination, and the information found in the pattern of results across specialties may be useful to residents and program directors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…It may be that medical school performance (e.g., years 1, 2, and 3) correlations with Step 3 are curriculum specific. Nonetheless, our results and interpretation are consistent with the findings of others [5,6,9]. Future work should include other institutions and larger samples which may also be profitably studied longitudinally, beyond residency.…”
Section: Limitationssupporting
confidence: 90%
See 2 more Smart Citations
“…It may be that medical school performance (e.g., years 1, 2, and 3) correlations with Step 3 are curriculum specific. Nonetheless, our results and interpretation are consistent with the findings of others [5,6,9]. Future work should include other institutions and larger samples which may also be profitably studied longitudinally, beyond residency.…”
Section: Limitationssupporting
confidence: 90%
“…Additionally, when they used Step 2 scores as a covariate, the performance of examinees in the narrowly focused postgraduate training programs tended to decrease as training progressed while for the broadly focused programs, performance increased. These patterns of results provide evidence for the validity of Step 3 as a measure of clinical skills [5]. In a more recent sample (n = 40,588 between 2007 and 2009), Feinberg et al [6] found a similar pattern of results on Step 3 for broadly focused (variety of patients under a variety of conditions) versus narrowly focused (limited exposure to a variety of patients and conditions) residencies.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous research indicates that Step 3 scores are related to the type and length of postgraduate training; specifically, examinees in residency programs who encounter a variety of patients under a variety of conditions (broadly focused programs) obtain higher scores than those in programs with more limited exposure to a variety of patients and conditions (narrowly focused programs), and that those in broadly focused residencies show score increases when Step 3 is taken later in residency training. [2][3][4] …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Multiple studies on the United States Medical Licensing Examination (USMLE) Step 3, the analogous examination used by MD degree-granting medical schools, [20][21][22] have found that performance on USMLE Step 3 depended in part on whether graduates sought a broad-based residency or one with a more narrow focus. [23][24][25] However, no studies could be identified that correlated COMLEX-USA Level 3 performance to admissions variables or performance in the COM curriculum other than to scores on Levels 1 and 2. If performance on Level 3 is to be used in accreditation decisions about COMs, and if admissions variables are at some point to be regarded as relating to Level 3 score, then these relationships need to be elucidated.…”
mentioning
confidence: 99%